Temporal variations in phytoplankton composition in the northeastern Sea of Marmara: potentially toxic species and mucilage event - TAS, SEYFETTIN; KUS, DUYSEN; YILMAZ, I. NOYAN (Mediterranean Marine Science, 2020)
Temporal variations in phytoplankton composition in the northeastern Sea of Marmara was investigated associated with physico-chemical variables from January 2004 to December 2007. The occurrence of potentially toxic species and a mucilage event was also evaluated during this study period. The confined upper layer of the Sea of Marmara is mesotrophic to eutrophic and has higher productivity when compared to the neighbouring Black Sea and Aegean Sea. 132 taxa in the micro-phytoplankton community were identified, 11 of which are known to be potentially toxic. The most abundant species were Pseudo-nitzschia species from diatoms and Prorocentrum micans from dinoflagellates. Potentially toxic species were more common at the coastal stations. The onset of a mucilage formation was observed in October 2007, and well-known mucilage producers such as Gonyaulax hyalina (reported as G. fragilis) and Thalassiosira gravida (reported as T. rotula) dominated the phytoplankton community during this event. A marked decrease in the number of species and diversity index following June 2007 and reported shifts in the zooplankton community during the same period points to probable cascading effects in the pelagic ecosystem of the Sea of Marmara.